Modelling Solar Irradiance Data for Energy Harvesting IoT Sensors - Choutka, Jan; Konecny, Jiri; Mikus, Miroslav; Bancik, Kamil; Prauzek, Michal; Konecny, Jaromir (Elektronika ir Elektrotechnika, 2024)
Managing energy in batteryless Internet of Things (IoT) nodes, especially in solar-powered mesh networks, presents significant challenges. This paper introduces an advanced solar irradiance model that simulates detailed daily energy profiles. The model considers various azimuth and elevation angles of solar panels, as well as cloud cover. Accurate simulation of daily energy production is critical for optimising the behaviour of solar-powered IoT nodes. The results highlight the utility of the model as a robust tool for research and simulations involving batteryless IoT devices, emphasising its enhanced capabilities for precise energy management and optimisation. This study offers a reliable framework for predicting and managing energy production in solar-powered IoT networks, thus supporting the development of more efficient and sustainable IoT systems.